2020
DOI: 10.1186/s13048-020-00717-5
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2, a protein repressed by miR-145, regulates proliferation, apoptosis, and migration in ovarian cancer cells

Abstract: RNA methylation can reverse the methylation modification at the RNA level, which is an extremely important epigenetic modification. The function and mechanism of YTHDF2, as a reader of m6A modification, in epithelial ovarian cancer (EOC) have not been elucidated so far. This study aimed to investigate how YTHDF2 and miR-145 modulated EOC progression through m6A modification. It demonstrated that YTHDF2 was significantly upregulated in EOC tissues compared with normal ovarian tissues. Further functional studies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…Acridine Orange assays show that high levels of miR-145 increase apoptosis of zebrafish embryonic cells, suggesting that NCCs may die before differentiation ( Figure 6 ). This finding agrees with data gathered in embryonic and cancer cultured cell lines, wherein miR-145 overexpression promotes apoptosis and reduces cell viability [ 16 , 34 , 69 , 77 , 78 ]. These observations as a whole could suggest that miR-145 participates in the control of cell death regulation in both normal and pathological conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Acridine Orange assays show that high levels of miR-145 increase apoptosis of zebrafish embryonic cells, suggesting that NCCs may die before differentiation ( Figure 6 ). This finding agrees with data gathered in embryonic and cancer cultured cell lines, wherein miR-145 overexpression promotes apoptosis and reduces cell viability [ 16 , 34 , 69 , 77 , 78 ]. These observations as a whole could suggest that miR-145 participates in the control of cell death regulation in both normal and pathological conditions.…”
Section: Discussionsupporting
confidence: 92%
“…In OC, YTHDF1 (reader) facilitates the expression of EIF3C [5] and the stem cell-like phenotype of cisplatin resistance [6] in a m6A-dependent manner, thereby strengthening tumorigenesis and metastasis. ALKBH5 (eraser) [7] and YTHDF2 (reader) [8,9] were shown to regulate the carcinogenesis of OC by modulating m6A levels. IGF2BP1 (reader) was demonstrated to augment the translation of serum response factor through m6A modification [10].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings confirmed that miR-145 inhibited ovarian cancer growth in vivo and in vitro [ 12 ]. MiR-145 blocked epithelial-mesenchymal transition of ovarian cancer cells by targeting FSCN1 [ 12 ], inhibited glutamine metabolism by targeting c-myc [ 14 ], inhibited the Warburg effect by targeting HK2 [ 16 ], and regulated RNA methylation by targeting YTHDF2 [ 24 ]. In order to test whether miR-145 was involved in the regulation of mitochondrial function, we then detected mitochondrial biogenesis by assessing the mtDNA copy number, ATP production, mitochondrial membrane potential, and mitochondrial-associated protein expression levels.…”
Section: Discussionmentioning
confidence: 99%